PERSPEKTIF SIYASAH TANFIDZIYAH TERHADAP IMPLEMENTASI TUGAS DAN KEWENANGAN BADAN PENGAWAS OBAT DAN MAKANAN DALAM PENGAWASAN PROMOSI PRODUK KOSMETIK DI E-COMMERCE - Ratu Balqis Maurila, Hacila; Nurnazli; Hasanah, Uswatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of e-commerce in Indonesia is currently encouraging cosmetic marketing via digital platforms. This condition gives rise to various legal problems, especially related to cosmetic promotions that use excessive promises, do not have distribution permits, and mislead customers. The aim of this research is to see how Food and Drug Supervisory Agency Regulation Number 18 of 2024 concerning Cosmetic Marking, Promotion and Advertising is used to monitor the promotion of cosmetic products on e-commerce websites. This study will also look at how the duties and authority of the Food and Drug Supervisory Agency are implemented from the perspective of siyasa tanfidziyah. The field research method used is a qualitative descriptive approach. Observation, interviews, documentation, and literature study are all methods used to obtain data sources. The inspection results show that BPOM has carried out supervision through monitoring labels and advertising, cyber supervision, public education, and taking action against cosmetic promotion violations. However, supervision is still being carried out.